Une lecture politique et historique du mythe de l’Ogre dans « le Roi des Aulnes » de Tournier - Racha Helmi (Beni-Suef University International Journal of Humanities and Social Sciences, 2022)
Le Roi des Aulnes is a novel by the French novelist Michel Tournier. He learned German. He studied philosophy at the Sorbonne and at the university of Tübingen and then became a journalist and a writer. Tournier is a French writer. He is the author of several novels. He published more than twenty books. He was a member of the Académie Goncourt and he won the Prix Goncourt for his novel Le Roi des Aulnes in 1970. It is also known as The Ogre.This novel is about a French prisoner in Germany who assists the Nazis during the World War II by searching for boys for a Nazi military camp. He recruits children to be Nazis in the belief that he is protecting them.The Ogre is a familiar character in mythology, folklore and fiction throughout the world. It is a kind of giant. An ogre is a legendary monster usually depicted as a large, hideous, man-like being that eats ordinary human being, especially infants and children. Tournier describes the World War II as the Ogre. Interrelation between myth and literature are very complex.